Produção pesqueira: uma caracterização socioeconômica dos pescadores artesanais do Porto dos Milagres, em Santarém - Pará no ano de 2019 - SOUSA, João Rodolfo Ramos de (Universidade Federal do Oeste do Pará, 2024)
This work aims to characterize, in an economic and social way, the artisanal fishermen who live in Bairro do Uruará, located in the municipality of Santarém-Pará. The applied method was bibliographical research, and application of a questionnaire with the artisanal fishermen who sell at the Porto dos Milagres Market, which took place in October 2019. In addition to demonstrating the social and economic importance that the Porto dos Milagres Market has on the fishermen, the survey also demonstrates the socioeconomic quality in which they live. The results show that the artisanal fishing activity is carried out mostly by men between 25 and 50 years old, with a very low female participation in this economic activity. Female participation in this activity is more frequent in activities underlying the main activity of fishing, such as, for example, the sale and recovery of tools used in fishing. The level of schooling of fishermen is low, with only four having completed primary education and only two having completed secondary education. The survey reveals that 76% of fishermen have a monthly income ranging between 300 and 400 reais. During the closed season there are some fishermen who carry out other activities in order to supplement the family income at the end of the month. Artisanal fishermen are committed to preserving the environment and local culture, as demonstrated in primary research, the activity is passed down from generation to generation. Knowledge of the hydrographic and climatic factors of the region where the fish is caught helps considerably in production. Artisanal fishing, despite the limitations and difficulties faced by fishermen, has been an important activity in the socioeconomic lives of fishermen who trade in Porto dos Milagres.